TEACHING TECHNIQUE USED BY THE TEACHER IN TEACHING ESP SPEAKING AT CIVIL ENGINEERING DEPARTMENT AT UNIVERSITY OF MUHAMMADIYAH MALANG - Lapele, Fitria (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2019)
Abstract This study used a descriptive qualitative design to gather the research data. While the instruments used in this study were observation and interview. The subject of this study was ESP Speaking teacher of Civil Engineering C Department at University of Muhammadiyah Malang.The result of this study showed that there were three techniques used by the teacher in teaching ESP Speaking at Civil Engineering C. The techniques were Brainstorming, Role Play, and Discussion. The students were very enthusiastic in learning speaking. They talked actively each other and confidently even though some of them still lack of vocabulary and frequently used the same vocabulary. Overall, these three techniques could effectively improve students speaking ability. Key terms: Teaching Technique, ESP, Speaking Abstrak Penelitian ini menggunakan desain deskriptif kualitatif. Untuk mengumpulkan data penelitian. instrumen yang digunakan dalam penelitian ini adalah observasi dan wawancara. Subjek penelitian ini adalah guru bahasa Inggris Jurusan Teknik Sipil C di Universitas Muhammadiyah Malang. Hasil penelitian ini menunjukkan bahwa ada tiga teknik yang digunakan oleh guru dalam mengajar di Teknik Sipil C. Tekniknya adalah Brainstorming, Peran Main, dan Diskusi. Para siswa sangat antusias dalam belajar berbicara. Mereka saling berbicara secara aktif dan percaya diri meskipun beberapa dari mereka masih kekurangan kosa kata dan sering menggunakan kosa kata yang sama. Secara keseluruhan, ketiga teknik ini dapat secara efektif meningkatkan kemampuan berbicara siswa. Kata kunci: Teknik Pengajaran, ESP, Berbicara